2018
DOI: 10.2196/12363
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anthropometrics on Step-Rate Thresholds for Moderate and Vigorous Physical Activity in Older Adults: Scientific Modeling Study

Abstract: Background Adults and older adults are recommended to engage in 150 minutes of moderate (MPA) to vigorous (VPA) aerobic physical activity (MVPA) per week, with the heuristic message of 3000 steps in 30 minutes (100 steps per minute [spm]). However, this message is based on adult populations, with a paucity of research on step-rate thresholds that correspond to absolute MVPA (moderate=3 metabolic equivalents [METs], vigorous=6 METs) and relative MVPA (moderate=40% estimated MET max … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
(52 reference statements)
0
29
0
Order By: Relevance
“…Abt et al [ 22 ] reported that sex (a reasonable proxy indicator of stature) did not significantly affect the cadence-intensity relationship in a sample of 20 young adults. In samples of adults older than that studied herein, Serrano et al [ 40 ] and O’Brien et al [ 41 ] reported that body weight explained 13%, and BMI and METs together (variance of BMI alone was not reported) explained 77% of the observed variance, respectively, of the cadence-intensity relationship (moderate intensity was defined by ≥40%VO 2 reserve and ≥ 40%MET max ) and that height, leg length or stride length showed no influence. Herein, the inclusion of sex, leg length, or BMI did not improve the variance explained by the segmented regression models in each age group.…”
Section: Discussionmentioning
confidence: 77%
“…Abt et al [ 22 ] reported that sex (a reasonable proxy indicator of stature) did not significantly affect the cadence-intensity relationship in a sample of 20 young adults. In samples of adults older than that studied herein, Serrano et al [ 40 ] and O’Brien et al [ 41 ] reported that body weight explained 13%, and BMI and METs together (variance of BMI alone was not reported) explained 77% of the observed variance, respectively, of the cadence-intensity relationship (moderate intensity was defined by ≥40%VO 2 reserve and ≥ 40%MET max ) and that height, leg length or stride length showed no influence. Herein, the inclusion of sex, leg length, or BMI did not improve the variance explained by the segmented regression models in each age group.…”
Section: Discussionmentioning
confidence: 77%
“…Physical activity intensity was determined using step rate thresholds for younger 13 and older adults. 14 All habitual sedentary and physical activity data were analyzed by a researcher blinded to participant popliteal outcomes. Our analysis program has previously demonstrated excellent inter-observer reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative measures include tracking total average steps per day for a week via a Step RX pedometer (Steps Count, StepRX, Ontario, Canada) [ 33 ]. A minimum of four consecutive days of wear-time had to be obtained to be considered as a valid measure [ 34 ].…”
Section: Methodsmentioning
confidence: 99%